Automated analysis of lateral river connectivity and fish stranding risks—Part 1: Review, theory and algorithm. Issue 2 (23rd December 2020) - Larrieu, Kenneth G.; Pasternack, Gregory B.; Schwindt, Sebastian
Abstract: Riverine fish stranding is of significant concern due to its potentially devastating impacts on fish populations already at risk. Because stranding is dependent on a wide range of biotic and abiotic factors, it is difficult to accurately identify and parameterize fish stranding risks for various river topographies, fish species/lifestages and flow ramping scenarios. This article presents a literature review, new concepts and a novel Python3 algorithm for post‐processing two‐dimensional hydrodynamic numerical model results to identify spatially explicit locations where fish stranding is likely, such as but not limited to downstream of hydropeaking facilities. Compared to previous stranding algorithms, this one is novel in its use of graph theory to find optimal fish escape routes and for its embedding in the free, open‐source river analysis software River Architect. Guided by biological parameter selection and supplied with two‐dimensional hydrodynamic model rasters, River Architect's Stranding Risk module is suitable for characterization of existing pool stranding risks, alternative flow regime and topographic design evaluation and post‐project assessment of rivers during flow recessions.